2021
DOI: 10.28991/cej-2021-03091712
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations on Flexural Behaviour of Prestressed Textile Reinforced Concrete Slabs

Abstract: Nowadays, concrete is mostly prestressed with steel. But the application of prestressing steel is restricted in a highly corrosive environment area due to corrosion of prestressing steel, leading to a reduction in strength and may cause sudden failure. Carbon textile is considered an alternate material due to its corrosive resistance property, high tensile strength, and perfectly elastic. Prestressing is also the only realistic way to utilize fully ultra-high tensile strength in carbon textile material. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The bending capacity of TRC could be improved by pre-stressing textiles. Test results showed that the first-crack load capacity of the specimens with pre-stressing textile was increased by 85%, compared with the non-prestressed specimens [119]. The flexural properties of 3D and 2D AR-glass textiles reinforced cementitious matrix are also compared.…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…The bending capacity of TRC could be improved by pre-stressing textiles. Test results showed that the first-crack load capacity of the specimens with pre-stressing textile was increased by 85%, compared with the non-prestressed specimens [119]. The flexural properties of 3D and 2D AR-glass textiles reinforced cementitious matrix are also compared.…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…Wiremesh is the latest breakthrough for reinforced concrete reinforcement using conventional methods. Wiremesh has been scientifically proven to reduce development time [18], [19].…”
Section: Wiremeshmentioning
confidence: 99%
“…Carbon textile is considered an alternate material due to its corrosive resistance property, high tensile strength, and being perfectly elastic. Prestressing is also the only realistic way to utilize fully ultra-high tensile strength in carbon textile material [30].…”
Section: Introductionmentioning
confidence: 99%